Real-time 3D integral imaging system using a faster elemental image generation method using GPU parallel processing - Islam, Md. Sifatul; Subhani, Mahfuze; Tareque, Mohd. Zishan; Rafi, M. Rashidur Rahman (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.